Konstruksi Identitas Citizenship pada Muslim di Yogyakarta - Muhammad Johan Nasrul Huda (Jurnal Psikologi Integratif, 2016)
Muslim is large social identity which represent to citizenship identification in Indonesia contexts. The dynamic of Yogyakarta Muslim that have special status is intersting to investigate about how they construct citizenship identity. The research used qualitative approach in which etnography and fenomenology as tool to understand of psychocultural reality that is main object in the research. Subjects are two elits of Muslim community in Yogyakarta. Data collection used depth interview and obeservation of participant to cover the problems. The result describes that Muslim construct their citizenship identity with extending of Islamic teaching categorization and elaboration in both of cultural and national. That is against to Turner’opinion which said that citizenship will be luck by religous identification. Furthermore Yogyakarta Muslim have been meaning of citizenship identity as transformative process from primodial categorization into inclusive categorization.